Meat tenderness: advances in biology, biochemistry, molecular mechanisms and new technologies. (March 2022) - Warner, Robyn D.; Wheeler, Tommy L.; Ha, Minh; Li, Xin; Bekhit, Alaa El-Din; Morton, James; Vaskoska, Rozita; Dunshea, Frank R.; Liu, Rui; Purslow, Peter; Zhang, Wangang
Abstract: Meat tenderness is an important quality trait critical to consumer acceptance, and determines satisfaction, repeat purchase and willingness-to-pay premium prices. Recent advances in tenderness research from a variety of perspectives are presented. Our understanding of molecular factors influencing tenderization are discussed in relation to glycolysis, calcium release, protease activation, apoptosis and heat shock proteins, the use of proteomic analysis for monitoring changes, proteomic biomarkers and oxidative/nitrosative stress. Each of these structural, metabolic and molecular determinants of meat tenderness are then discussed in greater detail in relation to animal variation, postmortem influences, and changes during cooking, with a focus on recent advances. Innovations in postmortem technologies and enzymes for meat tenderization are discussed including their potential commercial application. Continued success of the meat industry relies on ongoing advances in our understanding, and in industry innovation. The recent advances in fundamental and applied research on meat tenderness in relation to the various sectors of the supply chain will enable such innovation.